Physiological and Dietary Determinants of Iron Status in Spanish Vegetarians - Gallego-Narbón, Angélica (Nutrients, 2019)
Vegetarian diets may compromise iron status, as they provide non-haem iron which has low bioavailability. Spanish lacto-ovo vegetarians (n = 49) and vegans (n = 55) were recruited and haematological and biochemical iron parameters were analysed. Food and supplements consumption, body composition, physical activity, menstrual blood losses and hormonal contraceptive use were assessed. Four groups were studied: Iron deficiency anaemia (IDA), iron depletion (ferritin <15 ng/mL), iron deficiency (ferritin ≥15 to ≤30 ng/mL), and iron sufficiency (ferritin >30 ng/mL). IDA was uncommon (n = 5, 4.8%), 27.9% of participants were iron-depleted, and 30.8% were iron-deficient. Serum ferritin was lower in women than men (p < 0.001) and IDA and iron depleted individuals were all women. There were no differences attributed to diet type, time being vegetarian or physical activity. The menstrual period length was negatively associated with transferrin saturation (ρ = −0.364, p = 0.001) and hormonal contraceptive use (ρ = −0.276, p = 0.014). Iron supplements were consumed most frequently by IDA and iron-deficient subjects (p = 0.031). Conclusions: Iron status did not vary between lacto-ovo vegetarians and vegans and there was not an influence of the time following a vegetarian diet. Although men were iron-sufficient, iron deficiency was frequent in women, who should apply strategies to increase iron bioavailability, especially if they experience intense menstrual blood losses.